Some new Wyman–Leibovitz–Adler type static relativistic charged anisotropic fluid spheres compatible to self-bound stellar modeling - Murad, Mohammad Hassan; Fatema, Saba (© The Author(s) 2015. This article is published with open access at Springerlink.com, 2016)
This article was published in the The European Physical Journal C [© The Author(s) 2015. This article is published with open access at Springerlink.com] and the definite version is available at : http://10.1140/epjc/s10052-015-3737-6 The Journal's website is at: http://link.springer.com/article/10.1140/epjc/s10052-015-3737-6